PERKAWINAN ANAK DIBAWAH UMUR (Analisis Undang-undang Nomor 1 Tahun 1974 tentang Perkawinan) - Hernides Hernides; Muhsin Muhsin (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2020)
This paper describes the problem of child marriage that occurs in Indonesia. The results show that the government needs to revise Law Number 1 of 1974 concerning Marriage because the problem of underage marriage is still rife in low-income families, low education, and understanding of certain culture and religious values.